O Novo Coronavírus e o povo indígena Apurinã - Apurinã, Francisco (Instituto de Ciências Sociais da Universidade de Brasília, 2021)
The asymmetric relationship between environmental licensing and the license of spirits, which are connected to the physical and metaphysical, human and non-human environments, takes place when projects are built on top of places that are sacred to us Apurinã, such as ancestral cemeteries, stones, rivers, rocks, and other environments that are true dwelling places of shamanic agencies who have control over those. Furthermore, these agencies are responsible for the maintenance of the cosmos and the balance of living species, and, additionally, they are also sources that feed and nourish our bodies, minds and spirits. As these places and guardians are disrespected and insulted, they vanish or react in ways described by scientists as climate change, global warming, and more recently, the Anthropocene.